Translunate Perilunate Injuries—A Spectrum of This Uncommon Injury - Bain, Gregory Ian; Pallapati, Samuel; Eng, Kevin (Journal of Wrist Surgery, 2013)
Purpose To review a series of translunate perilunate dislocations to analyze the, mechanism of injury, diagnosis, management, and outcome.Methods A literature review and a survey of the International Wrist Investigators Workshop were performed to locate cases.Results Translunate perilunate injuries are rare. There is a spectrum of severity. The mechanism of injury is usually high-energy, and multiple fractures are the norm. High-energy mechanism, perilunate dislocation, comminuted lunate fracture and delayed presentation greater than 7 days are associated with a higher likelihood of a salvage procedure being required.Discussion Translunate injuries are a complex variant of perilunate dislocations. Early diagnosis is critical in understanding the complexity of the injury. Lunate fixation should be performed prior to bony and ligamentous stabilization of the proximal row. In delayed or highly comminuted cases, salvage procedures are the preferred option. Including a translunate arc in addition to the greater and lesser carpal arc would lead to a more inclusive classification.Level of Evidence Level IV.
Keywords: translunate; perilunate; dislocation; fracture